Comparison Learning Model AIR and TAI Combined With Cognitive Conflict Strategy Againts Active Learning and Concept Understanding - Dodik Septian Ferdiansyah; Syaad Patmanthara; Ilham Ari Elbaith Zaeni (JPP (Jurnal Pendidikan dan Pembelajaran), 2020)
There are several problems in the learning process of Basic Electricity and Electronics at SMK Negeri 8 Malang, including: (1) When learning takes place students do not pay attention and listen to the teacher when delivering material, (2) The teacher does not focus on learning activities to students, (3) Students are less active in asking and expressing his opinion about the material that has been taught. This study uses a variety of learning models and methods that can improve students' learning activeness and conceptual understanding, namely the Auditory, Intellectual, Repetition (AIR) learning model and the Team Assisted Individualization (TAI) learning model, each of which is combined with cognitive conflict strategies. The research design used a quasi experimental design with a non-equivalent control group design type. The data analysis technique consisted of normality test, homogeneity test, two mean similarity test, and hypothesis testing. The conclusion of this study is that the AIR learning model combined with cognitive conflict strategies is superior to the TAI learning model combined with cognitive conflict strategies